COVID-19 vaccine coverage, concerns, and preferences among Chinese ICU clinicians: a nationwide online survey. (3rd October 2021) - Huang, Weifeng; Shao, Xiaoping; Wagner, Abram L.; Chen, Yan; Guan, Baichu; Boulton, Matthew L.; Li, Bingzhe; Hu, Linjie; Lu, Yihan
ABSTRACT: Background: Clinicians in intensive care units (ICUs) have been prioritized for COVID-19 vaccination. We aim to understand the reasons behind vaccination refusal, and assess preferences for COVID-19 vaccines among Chinese ICU clinicians. Research design and methods: ICU clinicians throughout China's mainland were contacted to participate in an online survey. We compared concerns with vaccination status, and through a discrete choice experiment (DCE) assessed preferences for vaccines in terms of effectiveness, risk of adverse reactions, duration of immunity, and whether coworkers have been vaccinated. Results: Among 11, 951 ICU respondents from 252 prefecture-level regions, vaccination coverage was 75.4%, with an additional 9.2% not vaccinated but intending to, and 16.1% not vaccinated and not intending to. ICU clinicians not intending to be vaccinated significantly expressed more concerns about the speed of vaccine development (30.1%) and adverse reactions (65.9%). In the DCE, the only significant difference in preferences of a COVID-19 vaccine was for safety, with those not intending to have a stronger preference for a vaccine with fewer adverse reactions (OR = 4.49), compared to those already vaccinated (OR = 2.90) or those intending to vaccinate (OR = 3.46). Conclusion: Increasing vaccination coverage among Chinese ICU clinicians will require strong norms surrounding vaccination and transparency about safety information.